Tricorythodes tragoedia sp. nov. (Ephemeroptera: Leptohyphidae), a new species from Rio Doce and surrounding areas, southeastern Brazil - Souto, Paula Malaquias; Angeli, Kamila Batista; Salles, Frederico Falcão (Zootaxa, 2017)
A new species of Tricorythodes Ulmer (Ephemeroptera: Leptohyphidae) is described and illustrated based on nymphs and adults from the Doce River and surrounding areas in southeastern Brazil. Tricorythodes tragoedia sp. nov. is related to T. arequita Traver, T. mirca Molineri and T. sallesi Dias, Cabette & De Sousa, but its nymphs can be distinguished from these species by having a three-segmented maxillary palp with apical seta and one pair of submarginal denticles on the tarsal claws. Nymphs were collected from small to large rivers at altitudes of less than 100 m where they inhabit submersed substrates in areas with slow current. Nymphs and adults were found throughout the year.